39.4 EARLY AUDITORY PROCESSING IN SCHIZOPHRENIA: RELATIONSHIPS TO CLINICAL SYMPTOMS AND COGNITIVE REMEDIATION. (9th April 2019) - Mccleery, Amanda; Wynn, Jonathan; Jahshan, Carol; Marder, Stephen; Roach, Brian; Mathalon, Daniel; Green, M F
Abstract: Background: People with schizophrenia have clear impairments in early auditory processing. Mismatch negativity (MMN) is an auditory event-related potential that has been studied extensively in schizophrenia. MMN is elicited when an unexpected, low probability deviant auditory stimulus is presented after a repeated train of standard stimuli. The roving standard MMN paradigm is a modified version of MMN in which a series of standards is presented followed by a deviant, as in a typical (i.e., non-roving) MMN. However, the first appearance of the deviant stimulus is repeated over successive trials, so it becomes the new standard. This type of MMN varies the number of times the standard is presented. Exploration of predictive coding features of the MMN and its constituent components (i.e., repetition positivity, deviant negativity) can be optimized using a roving standard MMN paradigm. Methods: This presentation will cover three studies from our laboratory using MMN in people with schizophrenia. Study 1 compared roving standard MMN in 43 people with schizophrenia and 30 healthy comparison subjects over a two-week follow-up period. Study 2 compared roving standard MMN in 16 people with schizophrenia with recent auditory hallucinations, 14 without recent auditory hallucinations, and 20 healthy comparison subjects. Study 3 investigated non-roving MMN in 99 people with schizophrenia participating in a 12-week randomized control trial comparing two types of computerized cognitive remediation. Results: In the first study, we found that people with schizophrenia showed reduced MMN amplitude [F(1, 66.62)=4.14, p=0.05] due to reduced deviant negativity [F(1, 70.86)=4.39, p=0.04], but had normal repetition positivity [F(1, 73.12)=0.06, p=0.81]. Hence, they could establish a memory trace for the standards, but had abnormal prediction error signaling. In the second study, we found that schizophrenia patients with auditory hallucinations (but not non-hallucinators) failed to show an increase in negativity as the number of standards increased, indicating abnormalities in prediction error signaling are associated with hallucinations [F(2, 27)=3.98, p=0.03]. In the third study, MMN amplitude was associated with overall cognitive performance at the baseline assessment [r=-0.22, p=0.03]. Moreover, changes in MMN amplitude after 6 weeks of training predicted treatment effects on selected cognitive domains (e.g., verbal learning, reasoning / problem solving) after 12 weeks of training [r's>-0.38, p's<0.05]. Conclusions: Overall, these studies show the value of two versions of MMN for understanding clinical symptoms and treatment effects in schizophrenia.